2014
DOI: 10.1016/j.addbeh.2013.11.029
|View full text |Cite
|
Sign up to set email alerts
|

A web-based, health promotion program for adolescent girls and their mothers who reside in public housing

Abstract: This study tested a brief web-based, family-involvement health promotion program aimed at drug use, physical activity, and nutrition for adolescent girls, aged 10 to 12 years, who reside in public housing. Separately, girls (n = 67) and their mothers (n = 67) completed baseline measures online. Following baseline, 36 randomly assigned mother-daughter dyads jointly completed a 3-session, health promotion program online. Subsequently, all girls and mothers separately completed posttest and 5-month follow-up meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…In contrast, male caregivers were severely underrepresented (on average 5.0%), with only three studies including more than 10% male caregivers (Khanna et al, ; MacKenzie & Hilgedick, ; Yap et al, ). No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ). In most studies, the majority (>50%) of the sample were educated with post‐secondary qualifications ( n = 14, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; DuPaul et al, ; Fang et al, ; Hemdi & Daley, ; Jones et al, ; Khanna et al, ; Morgan et al, ; Sanders et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, male caregivers were severely underrepresented (on average 5.0%), with only three studies including more than 10% male caregivers (Khanna et al, ; MacKenzie & Hilgedick, ; Yap et al, ). No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ). In most studies, the majority (>50%) of the sample were educated with post‐secondary qualifications ( n = 14, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; DuPaul et al, ; Fang et al, ; Hemdi & Daley, ; Jones et al, ; Khanna et al, ; Morgan et al, ; Sanders et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published research on data collection using e-technologies is about using Electronic Data Capture (EDC) data entry systems (Babre, 2011) and Internet-based strategies for administering surveys and questionnaires for behavioral or health promotion studies (Stone et al, 2003; Geyer, et al 2011; Anton et al, 2012; Muzafkar et al, 2014; Schwinn et al, 2014). A novel approach for data collection that is facilitated by e-technologies is the ecological momentary assessment (EMA), which is a method designed to collect data in real time, recently extended to also deliver interventions for individuals with substance use disorders as well (Shiffman, 2009; Runyan et al, 2013; Epstein et al, 2014).…”
Section: 0 Integrating E-technologies Into Clinical Trial Design Imentioning
confidence: 99%
“…4449 A recent review found evidence that technology-based interventions, including web-based weight loss programs, may be efficacious in promoting weight loss and increasing physical activity in adolescents. 47 However, none of the studies reviewed integrated intervention components for targeting positive parenting strategies or cultural issues related to weight loss.…”
Section: Introduction To the Rationale For The Fit Trialmentioning
confidence: 99%
“…47 However, none of the studies reviewed integrated intervention components for targeting positive parenting strategies or cultural issues related to weight loss. Other research has demonstrated that web-based interventions may be relatively easy to disseminate and more likely to lead to improvements in health behaviors related to diet in ethnic minority 5053 and low income 49 adolescents. Schwinn and colleagues 49 tested a brief web-based, family-involvement health promotion program designed for adolescent girls living in public housing and their mothers.…”
Section: Introduction To the Rationale For The Fit Trialmentioning
confidence: 99%
See 1 more Smart Citation